2015
DOI: 10.1002/path.4586
|View full text |Cite
|
Sign up to set email alerts
|

Current mechanistic insights into the roles of matrix metalloproteinases in tumour invasion and metastasis

Abstract: The purpose of this review is to highlight the recent mechanistic developments elucidating the role of matrix metalloproteinases (MMPs) in tumour invasion and metastasis. The ability of tumour cells to invade, migrate, and subsequently metastasize is a fundamental characteristic of cancer. Tumour invasion and metastasis are increasingly being characterized by the dynamic relationship between cancer cells and their microenvironment and developing a greater understanding of these basic pathological mechanisms is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(154 citation statements)
references
References 100 publications
(118 reference statements)
5
144
0
1
Order By: Relevance
“…These factors have an important role in promoting tumor metastasis. A succession of studies are now providing a mechanistic basis, highlighting and reinforcing that specific MMPs are key in tumor invasion and metastasis through their catalytic and non-catalytic roles, including modulating tumor cell motility, promoting invadopodia formation, interactions of MMPs with pro-invasive pathways, sensing matrix stiffness and induction and maintenance of epithelial-mesenchymal transition (44). Therefore, hnRNP K simultaneously provided favorable conditions for tumor invasion and metastasis when upregulating MMPs expression.…”
Section: Hnrnp K Interacts With Signaling Molecules To Promote Tumorsmentioning
confidence: 93%
“…These factors have an important role in promoting tumor metastasis. A succession of studies are now providing a mechanistic basis, highlighting and reinforcing that specific MMPs are key in tumor invasion and metastasis through their catalytic and non-catalytic roles, including modulating tumor cell motility, promoting invadopodia formation, interactions of MMPs with pro-invasive pathways, sensing matrix stiffness and induction and maintenance of epithelial-mesenchymal transition (44). Therefore, hnRNP K simultaneously provided favorable conditions for tumor invasion and metastasis when upregulating MMPs expression.…”
Section: Hnrnp K Interacts With Signaling Molecules To Promote Tumorsmentioning
confidence: 93%
“…The cause of death caused by cancer is identified to be due to invasion and metastasis (Brown and Murray, 2015). In general, metastasis occurs when the unstable cells surrounding tumor in tissue environment.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased pH e enables cell migration (Stock and Schwab, 2009;Stock et al, 2005) and invasion (Estrella et al, 2013), in part by increasing the activity of acid-activated matrix metalloproteinases (MMPs) that dissolve cell-substrate adhesions (Brown and Murray, 2015;Yamamoto et al, 2015). Evidence suggests that NHE1 is a significant contributor to matrix degradation through local extracellular acidification or effects on MMP expression and localization (Lin et al, 2012;Putney and Barber, 2004).…”
Section: Migration and Metastasismentioning
confidence: 99%
“…We refer generally to cytosolic pH i , but the pH of various organelles is distinct from cytosolic pH (for review, see Casey et al, 2010) and cytosolic pH can be different in distinct parts of the cell, such as at lamellipodia (Stock et al, 2007) and invadopodia (Beaty et al, 2014). While the decreased pH e of cancer cells will be briefly discussed -as it relates to pH i and its role in enabling cell migration -detailed reviews on how decreased pH e alters cell-matrix remodeling can be found elsewhere (Stock and Schwab, 2009;Brown and Murray, 2015;Yamamoto et al, 2015;Hashim et al, 2011). Where known, we discuss the role of specific pH-sensors in the pH i -dependent cell process and molecular mechanisms for pH sensing.…”
Section: Introductionmentioning
confidence: 99%